FOXM1 predicts disease progression in non-muscle invasive bladder cancer - Rinaldetti, Sébastien; Worst, Thomas; Erben, Philipp (Journal of cancer research and clinical oncology, 2018)
The proto-oncogene forkhead box M1 (FOXM1) is associated with poor survival in many cancers. The impact of FOXM1 expression on progression-free survival (PFS) of non-muscle invasive bladder cancer (NMIBC) has not yet been investigated. The differential expression of FOXM1 between the different molecular NMIBC subtypes has further been assessed. Transcript levels of FOXM1 and MKI67 were determined in 460 NMIBC patients (UROMOL cohort) by RNA-Seq and validated in silico by the Chungbuk and Lund cohort (n = 277). FOXM1 and MKI67 cutoffs were identified by the minimal p value method. Variables were evaluated by multivariable Cox regression analyses in order to identify independent predictors. FOXM1 is an independent predictor for PFS superior to current histological, clinical and molecular staging methods. Patients with high FOXM1 expression have a 6- to 8-fold higher risk of progression in multivariable analysis (p < 0.03). Highest transcript levels were found in the Class 2 and genomically unstable molecular NMIBC subtype (p < 0.03). The proto-oncogene further positively correlated with tumor grade and stage. NMIBCs with high FOXM1 expression showed a PFS advantage when treated with intravesical BCG instillation. FOXM1 is a highly prognostic marker for disease progression of NMIBC superior to current histological, clinical and molecular staging methods and MKI67. It is mainly expressed in the Class 2 and genomically unstable molecular bladder cancer subtypes. Its role in drug resistance development makes FOXM1 valuable biomarker for NMIBC risk stratification.